Implementation of Braille-Assisted UNO Chemistry Card Media Integrated with Tourism Ethnochemistry Digital Content to Enhance the Scientific Literacy of Students with Visual Impairments - Dwi Bagus Rendy Astid Putera; Wiwin Puspita Hadi; Ana Yuniasti Retno Wulandari; Fajar Luqman Tri Ariyanto; Thoriqi Firdaus; Lisda Yasin Bakari (Jurnal Pendidikan IPA Indonesia, 2026)
Quality education must be equally accessible, especially to students with special needs, such as those with visual impairments. This study aims to enhance the scientific literacy skills of students with visual impairments by using Braille-assisted UNO Chemistry Card media integrated with tourism ethnochemistry digital content. The method employed an experimental design, utilizing a quasi-experimental approach. The type of experiment used was the Non-Equivalent Pretest-Posttest One-Group Design. The study population consisted of 15 Grade-XII students with visual impairments at SMALB YPAB Surabaya. The test instrument comprised six questions developed based on scientific literacy competency indicators. The results of the dependent T-test on the differences in scientific literacy abilities of students with visual impairments before and after using the Braille-Assisted UNO chemistry card game integrated with ethnochemical content in elemental chemistry learning for grade XII revealed a significance value of p < 0.05, so that H0 is rejected. Thus, the research hypothesis that there is a difference in the scientific literacy skills of students with visual impairments after using the braille-assisted UNO chemical element card game media in chemistry learning for grade XII is accepted. The n-gain score showed an increase in the scientific literacy skills of students with visual impairments by 33% (5 students) in the high category and 67% (10 students) in the medium category. Educational card games with braille letters integrated with ethnochemistry digital content for students with visual impairments are novel contribution of this research.